Laser Beam Polishing of Polymers: Selection of polymers suitable for laser‐based post processing of FLM‐printed parts. Issue 3 (24th May 2019) - Layher, Michel; Hopf, Andreas; Eckhardt, Lukas; Bliedtner, Jens
Abstract: Fused layer manufacturing (FLM) is an additive manufacturing process in which parts are built in layers by localized extrusion of molten polymer through a nozzle. It offers a high degree of geometrical flexibility as well as a wide range of suitable materials. Unfortunately, a characteristically high surface roughness is limiting the number of possible applications. The following article provides investigations regarding the remelting of FLM surfaces via laser beam polishing as an effective method for achieving a reduced roughness.